PENGARUH CITRA TUBUH DAN PENGELOLAAN DIRI TERHADAP KEMAMPUAN BEKERJASAMA DALAM PEMBELAJARAN EKONOMI - Yerico Yeriadi; Yohanes Harsoyo (Universitas Sanata Dharma, 2023)
This study aims to determine and analyze the effect of body image and self-management on student ability to cooperate in economics learning.This research is explanatory study conducted in July-August 2022 in SMA BOPKRI 2 Yogyakarta. The research population were students of class XI IPS 1 and XI IPS 2 covered 44 students. The research sample was 44 students. The research sampling technique was saturated sampling technique. The data collection technique was a questionnaire. The data analysis technique was multiple linear regression.The results of data analysis showed that: (1) body image had no effect on student ability to cooperate; (2) self-management had effect on student ability to cooperate; and (3) body image and management could be predictors of student ability to cooperate.Keywords: body image, self management, ability to cooperate